Advanced Expert CAE. Coursebook - Bell, J., Gower, R., Hyde, D. (Harlow Pearson Education Limited, 2005)
Advanced Expert CAE is flexible teaching programme which provides thorough preparation for the Cambridge Certificate in Advanced English examination, while continuing to develop and extend students language awareness and communicative skills.
Keywords: English Practice